Promoting learner autonomy in learning vocabulary for second-year students at Hai Phong Medical University - Trần, Thị Hòa (University of Languages and International Studies, 2017)
Learner autonomy, a concept promoted by Holec (1981) and others in the context of European language education, has become a favorite topic for analysis for the last twenty years. In many parts of the world, learner autonomy has been put forward as a goal to achieve (Pemberton et al., 1996; Sinclair et al., 2000; Littleet al., 2000; Benson, 2001). Several arguments may be used in favor of developing autonomy in language learners. For example, according to Naimen et al. (1978), autonomous learning is more effective than other approaches to learning, and Waite (1994) specifies that learners need to take charge of their own learning in order to make the most of available resources, especially outside the classroom